KOMUNIKASI GURU DAN ORANG TUA SISWA DALAM MENGOPTIMALKAN PEMBELAJARAN PADA MASA PANDEMI DI SDI AL-ITTIHAD TUKUM TEKUNG LUMAJANG - Chayati, Nur (IAIN Madura, 2021)
One of the keys to the successful implementation of the learning process during the COVID-19 pandemic is intensive communication between teachers and parents. Because without communication there will be obstacles because elementary school students still need the guidance of teachers and parents. The purpose of this study was to describe the communication between teachers and parents in optimizing learning during the pandemic at SDI Al-Ittihad Tukum Tekung Lumajang. This study uses a phenomenological qualitative approach. Collecting data in this study using interviews and documentation. To test the validity of the data obtained, the researcher used triangulation of data sources and triangulation of methods. The results of this study are: 1) Communication between teachers and parents at SDI Al-Ittihad during the covid 19 pandemic in carrying out the teaching and learning process using the sambang teacher program, namely visiting students' homes to carry out the learning process. Sometimes making small study groups of about 2-3 children per group which is carried out at students' homes and accompanied by their respective class teachers so that communication between teachers, parents, and students is more closely related. In addition, communication between teachers and parents is to form a whatsapp group for each class. 2) Obstacles or challenges faced by teachers and parents during the COVID-19 pandemic are limitations in using mobile phones, increased expenses due to having to buy quotas, and availability of network/internet signals.